GammaKnife versus VMAT radiosurgery plan quality for many brain metastases. (4th October 2018) - Potrebko, Peter S; Keller, Andrew; All, Sean; Sejpal, Samir; Pepe, Julie; Saigal, Kunal; Kandula, Shravan; Sensakovic, William F; Shridhar, Ravi; Poleszczuk, Jan; Biagioli, Matthew
Abstract: The purpose of this work was to compare dose distributions between two radiosurgery modalities, single‐isocenter volumetric modulated arc therapy (VMAT), and GammaKnife Perfexion (GK), in the treatment of a large number (≥7) of brain metastases. Twelve patients with 103 brain metastases were analyzed. The median number of targets per patient was 8 (range: 7–14). GK plans were compared to noncoplanar VMAT plans using both 6‐MV flattening filter‐free (FFF) and 10‐MV FFF modes. Parameters analyzed included radiation therapy oncology group conformity index (CI), 12, 6, and 3 Gy isodose volumes (V12 Gy, V6 Gy, V3 Gy), mean and maximum hippocampal dose, and maximum skin dose. There were statistically significant differences in CI (2.5 ± 1.6 vs 1.6 ± 0.8 and 1.7 ± 0.9, P  < 0.001, P  < 0.001), V12 Gy (2.8 ± 6.1 cc vs 3.0 ± 5.2 cc and 3.1 ± 5.4 cc, P  = 0.003, P  < 0.001), and V3 Gy (323.0 ± 294.8 cc vs, 880.1 ± 369.1 cc and 937.9 ±  vs 361.9 cc, P  = 0.005, P  = 0.001) between GK versus both 6‐MV FFF and 10‐MV FFF. No significant differences existed for maximum hippocampal or skin doses. In conclusion, highly optimized VMAT produced improved conformity at the expense of a higher V12 Gy and V3 Gy volume when compared with highly optimized GK.